Dr. Steven D. Schwaitzberg, associate professor of surgery at the School of Medicine, speaks to alumni at the School of Medicine. Photo 003 - Leonard, Spencer (Tufts Archival Research Center, 2008)
Dr. Steven D. Schwaitzberg, associate professor of surgery at the School of Medicine, speaks to alumni at the School of Medicine.